2022
DOI: 10.7600/jspfsm.71.523
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of physical characteristics in starters and non-starters in a Japanese university rugby football players

Abstract: The purpose of this study was to compare the characteristics of starters and nonstarters with respect to the anthropometric and physical fitness in a Japanese university rugby team. Our sample pool consisted of 54 players of the K University rugby team, who were registered for the official games (all 7 games/year) in 2018 and 2019. The starter group (26 players) comprised of players with more than 3 games/year while the non-starter group (28 players) comprised of players that registered for official games but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Forty-four articles did not describe any sports ISSs or ISGs, one did not report sports injury data, three had retrospective study designs, 11 described surveillance systems that had ceased operation or were not ongoing, and seven presented duplicated information. The search process identified 28 studies, including six English articles 23 24 25 26 27 28 and 22 Japanese articles 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 , that met the inclusion criteria. A flow diagram of the screening and selection process of the studies is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-four articles did not describe any sports ISSs or ISGs, one did not report sports injury data, three had retrospective study designs, 11 described surveillance systems that had ceased operation or were not ongoing, and seven presented duplicated information. The search process identified 28 studies, including six English articles 23 24 25 26 27 28 and 22 Japanese articles 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 , that met the inclusion criteria. A flow diagram of the screening and selection process of the studies is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Consensus statement on injury definitions and data collection procedures for studies of injuries in rugby union 38 39 40 42 43…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations